试论中唐常衮制书之文章价值 = Chang Gun’s imperial edicts and their Impact on prose writing in the Mid-Tang period - 曲景毅 Qu, Jingyi (2016)
文學史上一般認為，大曆文壇是相對岑寂的。大亂之後的唐王朝處於風雨飄搖之中，史稱：「明皇之失馭也，則祿山暴起於幽陵；至德之失馭也，則思明再陷於河洛；大曆之失馭也，則懷恩鄉導於犬戎。自三盜合從，九州羹沸，軍士膏於原野，民力殫於轉輸，室家相弔，人不聊生」。1安史之亂使得國家元氣大傷，朝廷對於各地的控制力大為削弱，藩鎮割據勢力甚囂塵上，所謂「四鎮三王」和李希烈、朱泚稱帝，西北邊患日益嚴重，吐蕃長年的襲擾，使朝廷疲憊不堪。「文變染乎世情，興廢繋乎時序」，幾經離亂，社會凋弊導致世情的變化，影響著文學的演進。在相對岑寂的大曆文壇，廟堂之上的秉筆者如常袞、楊炎，無疑是此期文章家中的佼佼者。After “AN & SHI’s Rebellion”安史之亂, people started to have resurgence consciousness and the Confucius thought of applying theory to reality is very common. CHANG Gun is a bright spot of prose writers in the relatively silent era. For the first time, the paper takes cognizance of CHANG Gun’s prose value in the Mid-Tang period. I analyze his imperial edicts’ value of acquaintanceship and history. Because “Ru shu” (Confucian skill) was canonized and practicability was great enhanced in his imperial edicts, new generation of “Wenru” (people who were good at Confucian and had writing skill and executive ability) was transferred and new imperial edict style was produced.